Self-regulated learning and engagement through emergency remote teaching in EFL undergraduate students - Oportus-Torres, René; Contreras-Soto, Yasmina; Sanhueza-Campos, Cristian; Maluenda-Albornoz, Jorge; Pérez-Villalobos, Christian; Quintanilla-Espinoza, Angie (Frontiers in Education, 2024)
An important concern of research on self-regulated learning is to determine the most effective methods for its instruction in different educational settings. This quasi-experimental study focuses on a 10-week intervention designed to develop self-regulation in undergraduate students learning English as a foreign language during emergency remote teaching. Levels of self-regulation and engagement were measured with a pre and post-test and control group design. Findings revealed that the intervention, as implemented in the study, was successful in raising self-regulated learning and in participants' recognizing the practical utility of tools acquired. On the other hand, while the level of engagement remained similar after the intervention, this was seen as a protective effect of the teaching-learning strategy on motivational states. This research underscores the importance of selfregulated learning training in higher education to allow for students' autonomy and agency, as well as connectedness with instructors and peers, especially during the harsh teaching conditions of sanitary confinement.